Keeping Our Hearts from Touching the Ground: HIV/AIDS in American Indian and Alaska Native Women - Walters, Karina L. (2011)
HIV/AIDS is a critical and growing challenge to American Indian and Alaska Native (AIAN) women’s health. Conceptually guided by the Indigenist Stress-Coping Model, this paper explores the historical and contemporary factors implicated in the HIV epidemic among AIAN women and the co-occurring epidemics of sexual violence and substance abuse. The authors also outline multiple indicators of resiliency in AIAN communities and stress the need for HIV prevention interventions for AIAN women to capitalize on cultural and community strengths.